2019
DOI: 10.1037/xan0000189
|View full text |Cite
|
Sign up to set email alerts
|

Operant evaluative conditioning.

Abstract: Two experiments investigated an evaluative transfer from actions producing pleasant and unpleasant outcomes to novel stimuli that were assigned to those actions in a subsequent stimulus-response task. Results showed that a fictitious social group was liked more when this group was assigned to the action previously associated with pleasant outcomes relative to the other action. This evaluative transfer from operant contingencies was observed although the actions did not generate outcomes during the stimulus-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The scale did not have a neutral point (i.e., zero was removed), because while piloting the task, participants reported that it felt strange to rate preference for meaningless strings of letters and had the tendency to give neutral ratings. Therefore, by removing the neutral point, we intended to constrain participants to attend even very subtle positive or negative feelings toward the strings (see Eder, Krishna, & Van Dessel, 2019, for a similar solution). After rating the string's valence, participants had to respond to an Awareness scale while the string was still on the screen.…”
Section: Methodsmentioning
confidence: 99%
“…The scale did not have a neutral point (i.e., zero was removed), because while piloting the task, participants reported that it felt strange to rate preference for meaningless strings of letters and had the tendency to give neutral ratings. Therefore, by removing the neutral point, we intended to constrain participants to attend even very subtle positive or negative feelings toward the strings (see Eder, Krishna, & Van Dessel, 2019, for a similar solution). After rating the string's valence, participants had to respond to an Awareness scale while the string was still on the screen.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, an inferential account proposes that people infer their liking of objects from their own behavior (Van Dessel, Eder, & Hughes, 2018;Van Dessel et al, 2018b). According to this view, participants observed that they stopped for an app and that stopping is unpleasant, thus negatively adjusting their evaluation of the app (for a more elaborate discussion, see Eder et al, 2019). Uncovering the exact mech-anism of how GNG influences evaluations may improve future applied training tasks to elicit stronger effects (e.g., Van Dessel et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…This change in liking could be conceived of as an effect of a regularity in the presence of a neutral stimulus (brand name) and a positive (approach) or negative (avoid) behavior. Such effects have been referred to as operant evaluative conditioning (De Houwer, 2007; Eder, Krishna, & Van Dessel, 2019).…”
Section: Distinctions Based On the Type Of Regularitymentioning
confidence: 99%